Resection of supratentorial brain metastases with intraoperative radiotherapy. Is it safe? Analysis and experiences of a single center cohort - Krauss, Philipp; Steininger, Kathrin; Motov, Stefan; Sommer, Bjoern; Bonk, Maximilian Niklas; Cortes, Abraham; Wolfert, Christina; Stueben, Georg; Shiban, Ehab; Kahl, Klaus Henning (Frontiers in Surgery, 2022)
Introduction Intraoperative Radiotherapy (ioRT) is an emerging treatment option in oncologic surgery for various diseases including intraaxial brain lesions to improve surgical outcome and accelerate the adjuvant oncologic therapy. Despite its use in glioma surgery, the application and data regarding ioRT in the treatment of brain metastases (BMs) is sparse. Here were report the largest series of supratentorial BMs treated with resection and ioRT according to functional outcome and adverse events. Methods We performed a retrospective chart review analysis of patients undergoing surgery for BMs following an interdisciplinary tumor board decision in every case with ioRT at our institution. Patient properties, functional status (Karnofsky Performance Score/KPS) before and after surgery as well as oncologic (disease, recursive partitioning analysis, lesion size) and operative parameters were analyzed until hospital discharge. Adverse events (AE) were recorded until 30 days after surgery and rated according to the Clavien Dindo Grading (CDG) scale. Results 70 patients (40 female) with various oncologic diseases were identified and analyzed. Six underwent prior RT. Mean age was 66 ± 11 years. Preoperative median KPS was 80% with a mean BM volume of 3.2 ± 1.2 cm3. Nine patients (13%) experienced in total 14 AEs, including 2 cases (3%) of postoperative death (CDG5) and 2 with new postoperative epilepsy necessitating additional pharmacotreatment (CDG2). Five patients suffered from new neurologic deficit (CDG1) not needing further surgical or medical treatment. After surgery, the neurological status in 7 patients (10%) deteriorated while it improved in 21 cases (30%). Patients experiencing AEs had longer hospitalization and poorer postoperative KPS mdn. 90 vs. 80%. There was no statistically significant deterioration of the functional status during the immediate postoperative course in the whole patient cohort. Conclusion Surgery for supratentorial BMs with ioRT seems safe and feasible. Further studies on the benefit regarding oncologic outcome need to be performed.